Fabrication and electromagnetic wave absorption property of quartz ceramics with a gradient distribution of BaTiO3. Issue 5 (1st April 2019) - Li, Xiangming; Yuan, Guojian; Zheng, Mengyao; Li, Rui; Meng, Zhen; Guo, Jia; Zhou, Guangyou
Abstract: Quartz ceramics with a uniform/gradient distribution of BaTiO3 (U/G–SO–BTO) are fabricated by cold pressing a powder blend with BTO followed by sintering and using a combined technique of spreading the powder blends with gradually increased BTO layer–by–layer and sintering. The electromagnetic wave absorption properties of these two ceramics are studied in detail. For U–SO–BTO samples, the primary electromagnetic reflection is strong due to the aggravated impedance mismatch at their surfaces. The electromagnetic wave reflectivity of U–SO–BTO could only reach −7.0 dB when the sample thickness is 6 mm and the BTO content is 8.0 wt%, and it decreases slightly to −8.1 dB when the sample thickness is increased to 10.0 mm and the BTO content is decreased to 5.0 wt% simultaneously. For G–SO–BTO samples, electromagnetic waves could enter with little reflection due to the weak surface impedance mismatch, and the electromagnetic waves entering these samples could propagate forward while being absorbed gradually with little reflection because of the weak impedance mismatch at the interfaces. The G–SO–BTO samples are promising excellent electromagnetic absorbing materials because their electromagnetic wave reflectivity could reach a level lower than −12.0 dB and could decrease further from –12.2 to −13.1 dB as the layer thickness increases from 1.0 to 2.0 mm.